Occupational Information-Seeking as a Function of Perception of Locus of Control and Other Personality Variables - Bernardelli, Antonio; De Stefano, Jack; Dumont, Florent (Canadian Journal of Counselling and Psychotherapy, 2012)
The relationships between internal-external locus of control, career maturity, occupational information-seeking, and sex were examined. Two hundred and forty 9th-grade students, 137 males and 103 females, were administered Rotter's Internal-External Locus of Control Scale and Crites' Career Maturity Inventory. Occupational information-seeking was assessed using a paper-and-pencil measure designed to elicit exploratory behavior of a vocational nature. Product-moment correlations, analyses of variance, and multiple regression analyses indicated that locus of control significantly correlated with career maturity. It was also found that career maturity was correlated significantly with occupational information-seeking behavior. Both significant and non-significant results were discussed.